Serum Retinol and Risk of Overall and Site-Specific Cancer in the ATBC Study. Issue 6 (15th October 2019) - Hada, Manila; Mondul, Alison M; Weinstein, Stephanie J; Albanes, Demetrius
Abstract: Retinol, the most biologically active form of vitamin A, might influence cancer-related biological pathways. However, results from observational studies of serum retinol and cancer risk have been mixed. We prospectively examined serum retinol and risk of overall and site-specific cancer in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study ( n  = 29, 104 men), conducted in 1985–1993, with follow-up through 2012. Serum retinol concentration was measured using reverse-phase high-performance liquid chromatography. Cox proportional hazards models estimated the association between baseline serum retinol quintile and overall and site-specific cancer risk in 10, 789 cases. After multivariable adjustment, higher serum retinol was not associated with overall cancer risk (highest vs. lowest quintile: hazard ratio (HR) = 0.97, 95% confidence interval (CI): 0.91, 1.03; P for trend = 0.43). Higher retinol concentrations were, however, associated with increased risk of prostate cancer (highest vs. lowest quintile: HR = 1.28, 95% CI: 1.13, 1.45; P for trend < 0.0001) and lower risk of both liver and lung cancers (highest vs. lowest quintile: for liver, HR = 0.62, 95% CI: 0.42, 0.91; P for trend = 0.004; and for lung, HR = 0.80, 95% CI: 0.72, 0.88; P for trend < 0.0001). No associations with other cancers were observed. Understanding the mechanisms that underlie these associations might provide insight into the role of vitamin A in cancer etiology.